2021
DOI: 10.1111/jocn.15991
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to interprofessional collaborative practice for community‐dwelling older adults: An integrative review

Abstract: Aims and Objectives The aim of this integrative review was to synthesise empirical reports of interprofessional collaborative practice (IPCP) for community‐dwelling older adults and uncover barriers and facilitators related to its success as a model of care for this population. Background IPCP is a model of care that has demonstrated positive outcomes for community‐dwelling older adults. However, a summary of barriers and facilitators to IPCP models has not been presented. Methods An integrative review using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…It became evident that funding and supporting regulations in the Netherlands were perceived as hindering for nationwide implementation of reablement. Current funding and reimbursement schemes fall short of covering all costs related to reablement programs and their accompanying interdisciplinary collaboration 56 . Consequently, this hinders care professionals from delivering care based on the client’s goals and needs, as the care provided is dictated by reimbursement criteria.…”
Section: Discussionmentioning
confidence: 99%
“…It became evident that funding and supporting regulations in the Netherlands were perceived as hindering for nationwide implementation of reablement. Current funding and reimbursement schemes fall short of covering all costs related to reablement programs and their accompanying interdisciplinary collaboration 56 . Consequently, this hinders care professionals from delivering care based on the client’s goals and needs, as the care provided is dictated by reimbursement criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Dear Editor, We read with great interest the article by Montano et al (2021) which identified barriers and facilitators related to the success of interprofessional collaborative practice (IPCP) as a care model for community-dwelling older adults. The authors importantly highlight that IPCP would be strengthened by introducing interprofessional education (IPE) training opportunities.…”
Section: Modifying Healthcare Student Curricula To Facilitate Interpr...mentioning
confidence: 99%
“…Innovative solutions need to be generated to address the practical difficulties of assessing the impact of IPE teaching on student's clinical practice. To date, most studies have only assessed student perspectives (Montano et al, 2021). Furthermore, in our experience, IPE in the context of community medicine has been lacking.…”
Section: Modifying Healthcare Student Curricula To Facilitate Interpr...mentioning
confidence: 99%
“…Because care supporting hospitalised older people's functioning is complex, it requires the services of a range of healthcare professionals working in concert [16][17][18]. Nurses, the largest group of professionals in Canada [19], can play a central role in supporting older people's functioning during a hospital stay [15,20].…”
Section: Introductionmentioning
confidence: 99%